The Palgrave Handbook of Bottom-Up Urbanism - Arefi, Mahyar; Kickert, Conrad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Who shapes our cities? In an age of increasing urban pluralism, globalization and immigration, decreasing public budgets, and an ongoing crisis of authority among designers and planners, the urban environment is shaped by a number of non-traditional stakeholders. The book surveys the kaleidoscope of views on the agency of urbanism, providing an overview of the various scholarly debates and territories that pertain to bottom-up efforts such as everyday urbanism, DIY urbanism, guerilla urbanism, tactical urbanism, and lean urbanism. Uniquely, this books seeks connections between the various movements by curating a range of views on the past, present, and future of bottom-up urbanism. The contributors also connect the recent trend of bottom-up efforts in the West with urban informality in the Global South, drawing parallels and finding contrast between social and institutional structures across the globe. The book appeals to urbanists in the widest sense of the word: those who shape, study, and improve our urban spaces. .
1. Introduction -- 2. Insurgency Meets Institution in Urban Placemaking -- 3. Guerrilla Architecture & Humanitarian Design -- 4. The Practice of Urbanism: From Public Participation to Community Development -- 5. Lean Urbanism is About Making Small Possible -- 6. Informal Urbanism and the American City -- 7. DIY Neighborhoods -- 8. The Self-Made City: Alternative Living and Urban Development Models -- 9. Bottom-up urbanism in Greece -- 10. Making Good Urbanism in Central Africa -- 11. New Trends in Bottom-up Urbanism & Governance: Reformulating Ways For Municipalities to Engage with Citizen-Led Urban Initiatives -- 12. Unplanned Creativity? Islam, Muslims and Urban Innovation in Germany -- 13. Endurance, Compliance, Victory: Learning from Informal Settlements in Five Iranian Cities -- 14. Space, Time & Agency on the Indian Street.
Keywords: Sociology, Urban; Urban Sociology